1999
DOI: 10.1097/00007890-199902270-00015
|View full text |Cite
|
Sign up to set email alerts
|

The Vanishing Importance of Age in Renal Transplantation

Abstract: Considering the improving results over time, there are, at this moment, no arguments for an age restriction for kidney transplant recipients or donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
40
0
4

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 11 publications
10
40
0
4
Order By: Relevance
“…7,10 Our results are in accordance with these reports; more than 50% of graft losses in older individuals were due to death with a functioning kidney, and 71.4% from cardiovascular or malignant diseases.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…7,10 Our results are in accordance with these reports; more than 50% of graft losses in older individuals were due to death with a functioning kidney, and 71.4% from cardiovascular or malignant diseases.…”
Section: Discussionsupporting
confidence: 92%
“…12 Some authors have argued that the better results reported in some series of older recipients may be due to less acute rejection in elderly recipients. 7,13 Consistent with these observations, we also found a significantly lower rejection rate among the older group, which may also contribute to the survival results.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A recent analysis of registry data indicated that transplant recipients 60-74 years old had better survival compared to similarly aged dialysis patients on the transplant waiting list (521). Although patient survival declines with increasing age, graft survival censored for death is better with increasing age (1019,1020). The net result is that there is similar overall graft survival for older compared to younger renal transplant recipients (1019,1020).…”
Section: Agementioning
confidence: 99%